Method for realizing pure pore size regulation and control of silicon carbide ceramic membrane
By using spray slurry and vacuum sintering technology, the pore size and filter layer thickness of the silicon carbide ceramic membrane are controlled, and the problem of high sintering temperature in the existing process is solved, making it difficult to prepare small-pore size membranes, and efficient and economical membrane pore size regulation and membrane performance improvement.
Patent Information
- Application Number
- CN202311138559.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-05
- Publication Date
- 2025-03-07
AI Technical Summary
In the existing silicon carbide ceramic film preparation process, the high sintering temperature makes it difficult to prepare a small pore-size film, and the process is complex and costly, which affects the purity and firmness of the film.
The spray slurry is composed of silicon carbide, sodium carboxymethylcellulose and dispersant. Through vacuum drying and vacuum sintering, the pore size and filter layer thickness of the silicon carbide ceramic membrane are adjusted to achieve pure quality control of the membrane.
Effective control of the pore size of existing silicon carbide ceramic membranes is achieved, the filtration flux and firmness of the membrane are improved, the process complexity and cost are reduced, and the film is guaranteed to have high purity.
Smart Images

Figure CN119569458A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for realizing the pore size purity regulation of a silicon carbide ceramic membrane, and belongs to the technical field of silicon carbide ceramic membranes. Background Art
[0002] In recent years, with the rapid development of membrane separation technology, membrane materials have been widely used in many fields. However, membrane materials have problems such as serious membrane pollution and short service life during the application process, which limits their promotion and application in the fields of fine chemicals, new energy development and environmental protection.
[0003] Existing membrane materials are mainly divided into two categories: organic membranes and inorganic membranes. Organic membranes are made of organic polymers. Due to the nature of the material, they have the disadvantages of small flux, short life, easy pollution, easy aging, easy damage, difficult recoil, and high pretreatment requirements. Inorganic membranes are made of inorganic materials and have strength and stability that organic membranes cannot match. They are especially resistant to high temperatures and pollution and have a long service life. They are currently a hot spot in the development of membrane materials. In addition to the common properties of inorganic membranes, pure silicon carbide ceramic membranes also have excellent properties such as resistance to strong acids and alkalis, high resistance to thermal shock, and a contact angle with water of nearly zero. They can operate stably for a long time in oil-water separation and harsh conditions, and are internationally recognized as ideal materials for the new generation of membrane products.
[0004] At present, the sintering method is mainly used to prepare silicon carbide ceramic membranes. The main sintering methods include reaction sintering, solid phase sintering, liquid phase sintering and recrystallization sintering. There is a certain gap in the performance of silicon carbide ceramic membranes obtained by different sintering processes. Among them: the silicon carbide ceramic membrane obtained by reaction sintering will contain a certain amount of free silicon. At high temperature, the evaporation of free silicon will cause the performance of the silicon carbide ceramic membrane to be affected; the sintering aids used in solid phase sintering and liquid phase sintering will soften or melt at high temperature, which will cause the performance of the obtained silicon carbide ceramic membrane products to decrease rapidly; and the silicon carbide ceramic membrane products obtained by reaction sintering, solid phase sintering and liquid phase sintering contain second phase impurities, which will also affect the performance of the silicon carbide ceramic membrane.
[0005] The recrystallization sintering process of silicon carbide ceramic membrane is the process of evaporation and condensation of fine silicon carbide particles on the neck of coarse particles. Compared with the reaction sintering method, solid phase sintering method and liquid phase sintering method, the advantages of recrystallization sintering silicon carbide are: due to the evaporation-condensation sintering mechanism, most of the recrystallized pores are through holes, so the silicon carbide ceramic membrane product obtained by the recrystallization method has a higher porosity, which is conducive to increasing the filtration efficiency; the recrystallization sintering process will not shrink, so the residual stress caused by shrinkage can be avoided to cause the ceramic membrane product to crack or deform; at the same time, the density of the sintered ceramic membrane particles is consistent with the density of the green body, so the particles can be closely stacked to obtain a ceramic membrane with a narrower pore structure. However, in the process of preparing silicon carbide ceramic membranes by recrystallization sintering, in order to ensure the strength of the silicon carbide ceramic membrane, the sintering temperature is usually as high as 1800°C or more. At this temperature, small particles of silicon carbide will be vaporized, so it is difficult to prepare silicon carbide ceramic membranes with small pores.
[0006] A pure silicon carbide ceramic membrane refers to a silicon carbide ceramic membrane with a silicon carbide purity greater than 99wt%. A method for preparing a pure silicon carbide membrane is disclosed in the patent with publication number CN103721578A and titled "A multi-channel asymmetric structure pure silicon carbide membrane and a method for obtaining the same". The patent firstly fires a substrate, then coats the substrate with a slurry containing silicon carbide particles multiple times and sinters the substrate to obtain a pure silicon carbide membrane. The filter layer thickness of the obtained pure silicon carbide membrane is 5 to 200μm, the filter pore size is 10 to 1000nm, and the pure water filtration flux is 1500 to 6500L·m -2 ·h -1 bar -1 When the pore size is 100nm, the pure water filtration flux is 2500L·m -2 ·h -1 bar -1 However, in the separation layer preparation process of this method: the solid content of the slurry used is 10-45wt%, and the solid content of the slurry is above 10%, which is costly and not conducive to industrial production. In addition, the process is complicated, which easily leads to the failure to ensure the firmness between the filter layers of the membrane. If an organic silicon polymer is added as a binder, impurities will be introduced, affecting the purity of the silicon carbide membrane. Summary of the invention
[0007] In view of the above problems existing in the prior art, the object of the present invention is to provide a method for achieving pure regulation of the pore size of silicon carbide ceramic membranes.
[0008] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is as follows:
[0009] A method for achieving pure quality control of pore size of silicon carbide ceramic membrane comprises the following steps:
[0010] a) adding silicon carbide, sodium carboxymethyl cellulose (CMC) and a dispersant into water in a mass ratio of (65-75):(13-15):(0.5-1.5), and milling the mixture uniformly to obtain a spray slurry having a silicon carbide content of 0.1-1 wt %;
[0011] b) spraying the spray slurry obtained in step a) onto the surface of the silicon carbide ceramic membrane to be regulated, and after natural drying, vacuum drying at 75-85° C. for 2-5 hours, and then placing it in a high-temperature furnace, vacuum sintering it at 800-1200° C. for 1-3 hours under vacuum conditions, and then placing it in a muffle furnace, oxidatively sintering it at 700-900° C. for 25-45 minutes in an air atmosphere.
[0012] In one embodiment, in step a), the silicon carbide is cubic silicon carbide (ie, β-SiC), and the particle size of the silicon carbide is 20 to 150 nm.
[0013] In a preferred embodiment, the particle size of the silicon carbide is 20 to 200 nm.
[0014] In one embodiment, in step a), the preparation of the spraying slurry comprises the following specific operations:
[0015] First, silicon carbide, sodium carboxymethyl cellulose and a dispersant are added to water in a mass ratio of (65-75):(13-15):(0.5-1.5), and ball-milled to obtain a high-solid content slurry with a silicon carbide content of 10%. The high-solid content slurry is then diluted with water to obtain a spray slurry with a silicon carbide content of 0.1-1wt%.
[0016] In a preferred embodiment, the ball milling speed is controlled at 350-400 r / min, the ball milling time is controlled at 3-5 hours, and the ball milling method is to rotate for 5-15 minutes, stay for 5-15 minutes, and alternate between forward and reverse rotations.
[0017] In one implementation scheme, in step b), during the spraying process, the spraying pressure is 0.4-0.6 MPa, and the spraying amount is 0.5-3 mL / s.
[0018] In one embodiment, in step b), the number of spraying passes is 1 to 4 times, preferably 1 to 3 times.
[0019] In one embodiment, in step b), the specific operation of vacuum sintering is as follows:
[0020] Under vacuum conditions, the temperature is raised to 800°C to 1200°C at a heating rate of 2 to 10°C / min, and sintered at this temperature for 1 to 3 hours.
[0021] In a preferred embodiment, in step b), the specific operation of vacuum sintering is as follows:
[0022] Under vacuum conditions, first heat the temperature to 500°C at a heating rate of 10°C / min and keep it warm for 20 minutes; then heat the temperature to 800°C at a heating rate of 5°C / min and keep it warm for 20 minutes; finally heat the temperature to 800°C~1200°C at a heating rate of 2~5°C / min, and sinter at this temperature for 1~3 hours.
[0023] In another preferred embodiment, in step b), the specific operation of vacuum sintering is as follows:
[0024] Under vacuum conditions, the temperature is first increased to 500°C at a heating rate of 10°C / min and kept at this temperature for 20 minutes; then the temperature is increased to 800°C at a heating rate of 5°C / min and sintered at this temperature for 1 to 3 hours.
[0025] In one embodiment, in step b), the specific operation of oxidation sintering is as follows:
[0026] In an air atmosphere, the temperature is raised to 700-900°C at a heating rate of 5-10°C / min, and sintered at this temperature for 25-45 minutes.
[0027] Compared with the prior art, the present invention has the following significant beneficial effects:
[0028] 1. The present invention can achieve pure regulation of the pore size of commercialized silicon carbide ceramic membranes. Not only is the pore size regulation effect significant (the pore size of commercialized silicon carbide ceramic membranes with a nominal pore size of 500nm can be regulated to less than 100nm), but the influence on the thickness of the filter layer of the silicon carbide ceramic membrane is small (the filter layer thickness of a 100nm pure silicon carbide ceramic membrane is only a few microns), the membrane layer has good firmness, and the filtration flux of pure water is high (the filtration flux of pure water of a 100nm pure silicon carbide ceramic membrane can exceed 6500L / m 2 ·h·bar);
[0029] 2. In the method of the present invention, the solid content of the spray slurry used is only 0.1-1wt%, and there is no need for repeated spraying and vacuum sintering. Not only is the process simple, the sintering temperature is low, and the film layer has good firmness; in particular, there is no need to add any sintering aids (for example, binders), so other impurities will not be introduced. Not only can the purity of the silicon carbide ceramic film be effectively guaranteed, but the method is simple, does not require special equipment, and is easy to scale up. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 The morphology of silicon carbide used in the present invention; wherein (a) is a SEM image of SiC-1, (b) is a SEM image of SiC-2, and (c) is a SEM image of SiC-3;
[0031] Figure 2Statistical graphs of the particle sizes of silicon carbide used in the present invention; wherein (a) is a statistical graph of the particle size of SiC-1, (b) is a statistical graph of the particle size of SiC-2, and (c) is a statistical graph of the particle size of SiC-3;
[0032] Figure 3 This is a DLS characterization diagram of the spray slurry used in the present invention;
[0033] Figure 4 is the XRD pattern of silicon carbide used in the present invention;
[0034] Figure 5 The morphology of the commercial silicon carbide ceramic membrane to be regulated used in the present invention; wherein (a) is a cross-sectional SEM image of the silicon carbide ceramic membrane to be regulated, and (b) is an enlarged cross-sectional SEM image of the silicon carbide ceramic membrane to be regulated;
[0035] Figure 6 The morphology of the pure (SiC-1) silicon carbide ceramic film obtained in Example 5 of the present invention; wherein (a) is a cross-sectional SEM image of the pure (SiC-1) silicon carbide ceramic film, and (b) is an enlarged cross-sectional SEM image of the pure (SiC-1) silicon carbide ceramic film;
[0036] Figure 7 The morphology of the pure (SiC-2) silicon carbide ceramic film obtained in Example 5 of the present invention; wherein (a) is a cross-sectional SEM image of the pure (SiC-2) silicon carbide ceramic film, and (b) is an enlarged cross-sectional SEM image of the pure (SiC-2) silicon carbide ceramic film;
[0037] Figure 8 These are morphology pictures of the pure (SiC-3) silicon carbide ceramic film obtained in Example 5 of the present invention; wherein, (a) is a cross-sectional SEM picture of the pure (SiC-3) silicon carbide ceramic film, and (b) is an enlarged cross-sectional SEM picture of the pure (SiC-3) silicon carbide ceramic film. DETAILED DESCRIPTION
[0038] The technical solution of the present invention is further described in detail and completely below in conjunction with the embodiments.
[0039] The present invention selects three kinds of silicon carbide particles with different particle sizes as raw materials for slurry preparation. The three kinds of silicon carbide particles with different particle sizes are marked as SiC-1, SiC-2 and SiC-3 respectively. Figure 1 shown.
[0040] Figure 2 Statistical diagram of the particle size of silicon carbide used in the present invention; wherein (a) is a statistical diagram of the particle size of SiC-1, (b) is a statistical diagram of the particle size of SiC-2, and (c) is a statistical diagram of the particle size of SiC-3; Figure 2It can be seen that the particle size statistics of SiC-1 is 35.20±11.28nm, the particle size statistics of SiC-2 is 50.54±15.47nm, and the particle size statistics of SiC-3 is 90.50±17.30nm.
[0041] Figure 3 DLS characterization diagram of the spray slurry used in the present invention; Figure 3 It can be seen that in the slurry, the statistical result of SiC-1 is 258.9±79.70nm, the statistical result of SiC-2 is 327.3±109.0nm, and the statistical result of SiC-3 is 403.0±143.7nm.
[0042] Figure 4 is the XRD pattern of silicon carbide used in the present invention; Figure 4 It can be seen that SiC-1, SiC-2 and SiC-3 used in the present invention are all cubic silicon carbide, that is, β-SiC.
[0043] The present invention uses the commercial silicon carbide ceramic membrane (original membrane) to be regulated as the skeleton, and its morphology is shown in the figure Figure 5 The initial retention rates are shown in Table 1.
[0044] Table 1 The retention rate of commercial silicon carbide ceramic membranes to be regulated for PS beads of different particle sizes
[0045] PS ball particle size 100nm 200nm 500nm Retention rate 12% 40% 97%
[0046] Among them, the interception rate detection method is as follows:
[0047] PS beads of different particle sizes and light intensities are selected to form a mixed solution. According to Lambert-Beer's law, when the concentration of PS beads is low, its light intensity is proportional to the concentration. Therefore, after drawing the standard curve, the concentration of PS beads can be calculated by the change in signal intensity. The relationship between the interception rate and the concentration of PS beads is calculated by the following formula:
[0048] R=(1-C t / C0)×100%;
[0049] Where: R is the retention rate (%); C0 and C t are the concentrations of fluorescent probes in the feed solution and permeate (μg / L), respectively.
[0050] When the interception rate is greater than 90%, the corresponding particle size of the PS beads is the filtration pore size (d 90 ), it can be seen from the above table that the filtration pore size (d 90 ) is 500nm.
[0051] Example 1
[0052] a) adding SiC-2 silicon carbide, sodium carboxymethyl cellulose and a dispersant into water in a mass ratio of 70:14:1, and then mixing them and uniformly milling them in a ball mill. The ball milling speed is 380 r / min, the ball milling time is 4 hours, and the ball milling method is to rotate for 10 minutes, stay for 10 minutes, and alternately rotate forward and reverse to obtain a high solid content slurry with a silicon carbide content of 10wt%, and then dilute the high solid content slurry with water to obtain a spray slurry with a silicon carbide content of 0.2wt%;
[0053] b) Spraying the spray slurry obtained in step a) onto the surface of the silicon carbide ceramic membrane to be regulated, spraying twice, and then naturally drying it, vacuum drying it at 80°C for 4 hours (to evaporate excess moisture in the separation layer), and then placing it in a high-temperature furnace, under vacuum conditions, first heating it to 500°C at a heating rate of 10°C / min, keeping it warm for 20 minutes, then heating it to 800°C at a heating rate of 5°C / min, keeping it warm for 20 minutes, and finally heating it to a sintering temperature of 1000°C at a heating rate of 5°C / min, and keeping it warm at the sintering temperature for 2 hours, then placing it in a muffle furnace, heating it to 900°C at a heating rate of 5°C / min in an air atmosphere, and keeping it warm at this temperature for 30 minutes.
[0054] After testing, the pure silicon carbide ceramic membrane obtained in this embodiment has a retention rate of 93% for 100nm PS beads and a retention rate of 98% for 200nm PS beads. 90 ) is 100nm.
[0055] Example 2
[0056] The difference between this embodiment and embodiment 1 is that the solid content (the content of silicon carbide) of the spray slurry used is 0.5wt%, 0.2wt%, 0.1wt% and 0.05wt% respectively. The retention rate of the pure silicon carbide ceramic membrane obtained in this embodiment for 100nm PS beads is shown in Table 2.
[0057] Table 2
[0058] Solid content Original film 0.50wt% 0.20wt% 0.10wt% 0.05wt% 100nm PS beads retention rate 12% 94% 93% 65% 30%
[0059] It can be seen from Table 2 that after the slurry containing silicon carbide is sprayed on the surface of the silicon carbide ceramic membrane (original membrane) to be regulated, the pores of the original membrane are well modified, and the solid content of the sprayed slurry has a certain influence on the regulation effect of the pore size of the silicon carbide ceramic membrane.
[0060] Example 3
[0061] The difference between this embodiment and embodiment 1 is that in step b), the spraying slurry is sprayed on the surface of the silicon carbide ceramic membrane to be regulated 1, 2, 3, and 4 times respectively. The retention rates of the pure silicon carbide ceramic membrane obtained in this embodiment for 100nm PS beads and 200nm PS beads are shown in Table 3.
[0062] Table 3
[0063] Spraying times 1 2 3 4 100nm PS beads retention rate 78% 93% 95% 39% 200nm PS beads retention rate 91% 98% 98% 81%
[0064] As can be seen from Table 3, too few spraying times will lead to uneven film layer, and too many spraying times will cause the slurry during the later spraying to blow away the silicon carbide particles sprayed in the previous spraying, and increase the cost. Considering factors such as comprehensive cost and pore size, spraying 2 to 3 times is better.
[0065] Example 4
[0066] The difference between this embodiment and embodiment 1 is that the vacuum sintering temperatures in step b) are 800°C, 900°C, 1000°C, 1100°C, and 1200°C, respectively, and the heating rate is 2°C / min when the temperature is raised from 800°C to the sintering temperature. The retention rates of the pure silicon carbide ceramic membrane obtained in this embodiment for 100nm PS beads and 200nm PS beads are shown in Table 4.
[0067] Table 4
[0068] Vacuum sintering temperature 800℃ 900℃ 1000℃ 1100℃ 1200℃ 100nm PS beads retention rate 77% 89% 95% 87% 58% 200nm PS beads retention rate 96% 96% 97% 93% 95%
[0069] It can be seen from Table 4 that the vacuum sintering temperature has a certain influence on the modification effect of the original membrane pores. If the sintering temperature is too low, the membrane layer will be unreliable, thus affecting the modification effect on the pores. If the temperature is too high, it will not only increase the sintering cost, but also as the temperature rises, the degree of gasification of small particles will deepen, and when they re-solidify on the surface of large particles, the modification effect on the pores will be weakened. The vacuum sintering effect at 900-1100℃ is relatively good.
[0070] Example 5
[0071] The difference between this embodiment and embodiment 1 is that the silicon carbides used are SiC-1, SiC-2, and SiC-3, respectively. When SiC-1 is used, the solid content of the spray slurry is 0.28wt%; and, during the vacuum sintering process in step b), when the temperature is increased from 800°C to 1000°C, the heating rate is 2°C / min. The retention rates of the pure silicon carbide ceramic membrane obtained in this embodiment for 20nm PS beads, 100nm PS beads, and 200nm PS beads are shown in Table 5.
[0072] Table 5
[0073] Silicon carbide particles SiC-1 SiC-2 SiC-3 Solid content 0.28wt% 0.20wt% 0.20wt% 20nm PS beads retention rate 71% 45% 30% 100nm PS beads retention rate 96% 95% 96% 200nm PS beads retention rate 98% 97% 98%
[0074] It can be seen from Table 5 that when the solid content of the spraying slurry is 0.2-0.30wt%, the SiC-1 slurry, SiC-2 slurry and SiC-3 slurry with three different particle sizes all have a good modification effect on the pore size of the original membrane.
[0075] The morphologies of the pure silicon carbide ceramic films obtained in this embodiment are as follows: Figures 6 to 8 As shown by Figure 6 As can be seen from the cross-sectional SEM images in (a), 7(a), and 8(a), the pure silicon carbide ceramic membrane obtained in this embodiment has a very thin separation layer on the surface, and the thickness of the separation layer is about 10 μm. Figure 6 It can be seen from the cross-sectional enlarged SEM images in (b), 7(b) and 8(b) that the surface of the pure silicon carbide ceramic membrane obtained in this embodiment is filled with small particles, and as the particle size of the silicon carbide particles increases, the porosity of the membrane layer gradually increases.
[0076] In addition, after testing, the filtration pore sizes of the pure (SiC-1) silicon carbide ceramic membrane, the pure (SiC-2) silicon carbide ceramic membrane, and the pure (SiC-3) silicon carbide ceramic membrane obtained in this embodiment all reached 100nm, while the nominal pore size of the silicon carbide ceramic membrane to be regulated used in the present invention is 500nm. It can be seen that the present invention can effectively modify and reduce the original membrane pore size of the ceramic membrane to obtain a pure silicon carbide ceramic membrane with a small pore size.
[0077] The pure silicon carbide ceramic membranes obtained in this example were placed in beakers containing 80 mL of ultrapure water and subjected to ultrasound for 10 minutes. The turbidity changes of the ultrapure water and the changes in the retention rate of the SiC ceramic membrane for 100 nm PS beads were compared to investigate the firmness of the pure silicon carbide ceramic membranes. The results of the firmness test are shown in Table 6.
[0078] Table 6
[0079] Silicon carbide particles SiC-1 SiC-2 SiC-3 Original film Heating rate from 800 to 1000°C 2℃ / min 2℃ / min 2℃ / min - Turbidity (NTU) 0.000 0.000 5.580 52.610 Retention rate of 100 nm PS beads before ultrasound 96% 95% 96% 12% Retention rate of 100 nm PS beads after ultrasound 93% 88% 91% 8%
[0080] It can be seen from Table 6 that after 10 minutes of ultrasonic treatment of the pure silicon carbide ceramic membrane obtained in this embodiment, the turbidity of water did not change significantly, and the reduction in the interception rate was also within an acceptable range, indicating that the pure silicon carbide ceramic membrane of the present invention has good firmness.
[0081] In addition, the results of testing the pure water flux of the pure silicon carbide ceramic membrane obtained in this embodiment are shown in Table 7.
[0082] Table 7
[0083] Membrane Type Original film SiC-1 SiC-2 SiC-3 100nm PS beads retention rate 12% 96% 95% 96% <![CDATA[Pure water flux (L / h·m 2 ·bar)]]> 8598.73 5732.48 3999.41 6878.98
[0084] It can be seen from Table 7 that the pure silicon carbide ceramic membrane obtained by the present invention not only has a significantly reduced pore size compared to the original membrane, but also maintains a relatively high water flux.
[0085] Finally, it should be pointed out that the above are only some preferred embodiments of the present invention and should not be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above contents of the present invention all fall within the scope of protection of the present invention.
Claims
1. A method for achieving pore size control of silicon carbide ceramic membrane, characterized in that: The steps include: a) adding silicon carbide, sodium carboxymethyl cellulose and a dispersant in a mass ratio of (65-75):(13-15):(0.5-1.5) into water, and ball-milling the mixture to obtain a spray slurry having a silicon carbide content of 0.1-1 wt %; b) spraying the spray slurry obtained in step a) onto the surface of the silicon carbide ceramic membrane to be regulated, and after natural drying, vacuum drying at 75-85° C. for 2-5 hours, and then placing it in a high-temperature furnace, vacuum sintering it at 800-1200° C. for 1-3 hours under vacuum conditions, and then placing it in a muffle furnace, oxidatively sintering it at 700-900° C. for 25-45 minutes in an air atmosphere.
2. The method according to claim 1, characterized in that: In step a), the silicon carbide is cubic silicon carbide.
3. The method according to claim 1, characterized in that: In step a), the preparation of the spray slurry includes the following specific operations: First, silicon carbide, sodium carboxymethyl cellulose and a dispersant are added to water in a mass ratio of (65-75):(13-15):(0.5-1.5), and ball-milled to obtain a high-solid content slurry with a silicon carbide content of 10%. The high-solid content slurry is then diluted with water to obtain a spray slurry with a silicon carbide content of 0.1-1wt%.
4. The method according to claim 1, characterized in that: In step b), during the spraying process, the spraying pressure is 0.4-0.6 MPa, and the spraying amount is 0.5-3 mL / s.
5. The method according to claim 1, characterized in that: In step b), the number of spraying times is 1 to 4 times.
6. The method according to claim 1, characterized in that: In step b), the specific operation of vacuum sintering is as follows: Under vacuum conditions, the temperature is raised to 800°C to 1200°C at a heating rate of 2 to 10°C / min, and sintered at this temperature for 1 to 3 hours.
7. The method according to claim 1, characterized in that: In step b), the specific operation of vacuum sintering is as follows: first, heat to 500°C at a heating rate of 10°C / min and keep warm for 20 minutes; then heat to 800°C at a heating rate of 5°C / min and keep warm for 20 minutes; finally, heat to 800°C~1200°C at a heating rate of 2~5°C / min, and sinter at this temperature for 1~3 hours.
8. The method according to claim 1, characterized in that: In step b), the specific operation of vacuum sintering is as follows: first, heat up to 500°C at a heating rate of 10°C / min and keep warm for 20 minutes; then heat up to 800°C at a heating rate of 5°C / min and keep warm at this temperature for 1 to 3 hours.
Citation Information
Patent Citations
Multi-channel pure silicon carbide film with asymmetric structure and preparation method for multi-channel pure silicon carbide film
CN103721578A
Preparation method of pure silicon carbide porous ceramic membrane
CN104261867A
Plate type silicon carbide nano-ceramic filtering filter element and production method thereof
CN108771912A
High-flux silicon carbide ceramic filtering membrane and preparation method thereof
CN113121241A
Preparation method of low-temperature reaction-sintered silicon carbide ceramic membrane
CN113999046A
Cited By
Coating slurry, low-impedance diaphragm and preparation method of low-impedance diaphragm
CN120810178A
A coating slurry, low impedance separator and method of making the same
CN120810178B
Tubular silicon carbide ultrafiltration membrane based on controllable filling method and preparation method thereof
CN121466803A